Who Pays for Universal Service? : When Telephone Subsidies Become Transparent. - Crandall, Robert W. (Brookings Institution Press, 2010)
In virtually every country, the price of residential access to the telephone network is kept low and cross-subsidized by business services, long distance calling, and various other telephone services. This pricing practice is widely defended as necessary to promote ""universal service, "" but Crandall and Waverman show that it has little effect on telephone subscriptions while it has major harmful effects on the value of all telephone service. The higher prices for long distance calls reduce calling, shift the burden of paying for the network to those whose social networks are widely dispersed.